Real-world tolerability of biosimilar bevacizumab-awwb compared to bevacizumab in patients with cancer at an academic medical center. Issue 28 (1st October 2022) - Alhaja, Maher; Tsourounis, Candy; Ho, Hansen; Fong, Richard
Abstract : 322 Background: Bevacizumab-awwb and bevacizumab are vascular endothelial growth factor (VEGF) inhibitors that are commonly combined with other oncolytic agents for the treatment of various malignancies. Real-world outcomes and financial impact of biosimilar use are limited, particularly for oncologic indications. In patients with non-small cell lung cancer, bevacizumab-awwb and bevacizumab demonstrated similar clinical efficacy and safety. Bevacizumab-awwb outcomes in other cancer subtypes are lacking. The purpose of this study is to compare the safety and financial impact associated with the utilization of biosimilar bevacizumab-awwb vs bevacizumab. Methods: This is an IRB-approved, single-center, retrospective cohort study including adult cancer patients who were initiated on bevacizumab-awwb or bevacizumab between June 2019 and May 2021. Eligible patients for bevacizumab-awwb treatment must have been naïve to bevacizumab treatment. Patients switching from bevacizumab to bevacizumab-awwb or participating in clinical trials were excluded. Common Terminology Criteria for Adverse Events Version 5 was used for safety outcomes assessment. The primary safety outcome was new-onset, grade ≥ 2+ hypertension (HTN). The secondary safety outcomes include grade ≥ 2+ proteinuria, hemorrhage, and gastrointestinal perforation, and cost using the average wholesale price for drug acquisition. Results: In this study, 377 patients were included with 200 Bevacizumab and 177 Bevacizumab-awwb patients. There were 11 cancer types with similar baseline characteristics among both groups except for ovarian and hepatocellular carcinoma. Although there was no significant difference in grade ≥ 2+ HTN, initiation of new antihypertensive therapy was found to be greater in the bevacizumab arm (p = 0.002). Grade 2 proteinuria was observed to be lower in the Bevacizumab-awwb arm (p = 0.01). There were no significant differences in other safety outcomes. In 2020, bevacizumab-awwb utilization accounted for 34% of bevacizumab orders, saving 167, 000. If bevacizumab-awwb utilization increased to 75%, approximately 400, 000 can be saved per year. Conclusions: In this real-world analysis, bevacizumab-awwb demonstrated a comparable safety profile to bevacizumab in regards to grade ≥ 2+ hypertension, proteinuria, hemorrhage and gastrointestinal perforation regardless of primary cancer type. Replacing Bevacizumab for Bevacizumab-awwb lowered drug acquisition costs.